(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
The advent of digital systems for the production and transmission of information decisively influences human progress and represents the future in any field of social life. In order to survive, organizations must correlate the objectives to the new trend of the society based on information, deeply marked by globalization. In recent years new computational paradigm were proposed and adopted. These include Cloud computing. Together with the stabilization of technologies related to Cloud computing, SQL databases have become more attractive due to native support for scalability and distributed architecture and the fact that many of these can be offered as services. The paper presents a few important aspects about cloud computing and proposed a new database designed to be implemented in cloud.Â We offer a new model and an example of implementing in Romanian medicine[1]. Â [1] This is an extended paper of the article presented at The 15th International Conference on Informatics in Economy, Cluj-Napoca, 2016.